The outcome of a preoperative one-minute sit-to-stand test is associated with ventilation time after cardiac surgery - Gofus, Jan; Vobornik, Martin; Koblizek, Vladimir; Pojar, Marek; Vojacek, Jan (Scandinavian cardiovascular journal, 2021)
Objectives. The One-minute Sit-To-Stand Test (STST) is a relatively novel physical performance test in the field of pulmonology. It measures the exercise tolerance of the patient. In this pilot study, we evaluated its predictive value for the postoperative course in cardiac surgery patients. Design. This was a prospective observational cohort study of patients undergoing elective aortic valve replacement. STST was applied in the patients, along with pulmonary function testing, a day prior to surgery, on postoperative day 7, and 3 months after surgery. A Short Form-36 health related quality of life survey (SF-36) was also included. The patients were divided into two groups according to the preoperative STST outcome: group A (≤20 repetitions, n = 12), and group B (>20 repetitions, n = 18). Results. We enrolled 30 patients in the study between May 2017 and May 2019. No complication were observed during the STST. The standard perioperative measures were identical for both groups. However, group A exhibited a significantly longer artificial ventilation time, as well as worse pulmonary function (VC, FVC, TLCO), on postoperative day 7. Concerning the SF-36, group A displayed a worse pre- and postoperative evaluation in both physical functioning and vitality. Conclusions. STST is a short and practical physical performance test that could enable a better prediction of the postoperative course after cardiac surgery. Patients with lower preoperative STST performance may require longer postoperative artificial ventilation, as they may present worse in some parameters of pulmonary functions and quality of life. However, these findings must be corroborated in larger studies.
Keywords: kardiochirurgické výkony; zátěžový test; umělé dýchání; Humans; risk assessment; exercise tolerance; physical performance test; lidé; Exercise Test; pilotní projekty; časové faktory; Cardiac Surgical Procedures; Pilot Projects; předoperační péče; Sit-to-stand test; cardiac surgery; Preoperative Care; Respiration, Artificial; prospektivní studie; Time Factors; Prospective Studies